Four Kinetically Distinct Depolarization-activated K(+) Currents in Adult Mouse Ventricular Myocytes - Xu, Haodong (The Rockefeller University Press, 1999)
In the experiments here, the time- and voltage-dependent properties of the Ca(2+)-independent, depolarization-activated K(+) currents in adult mouse ventricular myocytes were characterized in detail. In the majority (65 of 72, ≈ 90%) of cells dispersed from the ventricles, analysis of the decay phases of the outward currents revealed three distinct K(+) current components: a rapidly inactivating, transient outward K(+) current, I(to,f) (mean ± SEM τ(decay) = 85 ± 2 ms); a slowly (mean ± SEM τ(decay) = 1,162 ± 29 ms) inactivating K(+) current, I(K,slow); and a non inactivating, steady state current, I(ss). In a small subset (7 of 72, ≈ 10%) of cells, I(to,f) was absent and a slowly inactivating (mean ± SEM τ(decay) = 196 ± 7 ms) transient outward current, referred to as I(to,s), was identified; the densities and properties of I(K,slow) and I(ss) in I(to,s)-expressing cells are indistinguishable from the corresponding currents in cells with I(to,f). Microdissection techniques were used to remove tissue pieces from the left ventricular apex and from the ventricular septum to allow the hypothesis that there are regional differences in I(to,f) and I(to,s) expression to be tested directly. Electrophysiological recordings revealed that all cells isolated from the apex express I(to,f) (n = 35); I(to,s) is not detected in these cells (n = 35). In the septum, by contrast, all of the cells express I(to,s) (n = 28) and in the majority (22 of 28, 80%) of cells, I(to,f) is also present. The density of I(to,f) (mean ± SEM at +40 mV = 6.8 ± 0.5 pA/pF, n = 22) in septum cells, however, is significantly (P < 0.001) lower than I(to,f) density in cells from the apex (mean ± SEM at +40 mV = 34.6 ± 2.6 pA/pF, n = 35). In addition to differences in inactivation kinetics, I(to,f), I(to,s), and I(K,slow) display distinct rates of recovery (from inactivation), as well as differential sensitivities to 4-aminopyridine (4-AP), tetraethylammonium (TEA), and Heteropoda toxin-3. I(K,slow), for example, is blocked selectively by low (10–50 μM) concentrations of 4-AP and by (≥25 mM) TEA. Although both I(to,f) and I(to,s) are blocked by high (>100 μM) 4-AP concentrations and are relatively insensitive to TEA, I(to,f) is selectively blocked by nanomolar concentrations of Heteropoda toxin-3, and I(to,s )(as well as I(K,slow) and I(ss)) is unaffected. I(ss) is partially blocked by high concentrations of 4-AP or TEA. The functional implications of the distinct properties and expression patterns of I(to,f) and I(to,s), as well as the likely molecular correlates of these (and the I(K,slow) and I(ss)) currents, are discussed.